Fatal lactic acidosis in hepatitis B virus-associated decompensated cirrhosis treated with tenofovir: A case report. Issue 25 (June 2017) - Jung, Tae Yang; Jun, Dae Won; Lee, Kang Nyeong; Lee, Hang Lak; Lee, Oh Young; Yoon, Byung Chul; Choi, Ho Soon
Abstract: Rationale: Recently tenofovir disoproxil fumarate (TDF) has been widely used as a first-line therapy for chronic hepatitis B (CHB) infection. Although TDF demonstrates successful viral suppression, the possibility of renal failure and lactic acidosis has been proposed with TDF administration, especially in human immunodeficiency virus co-infected patients. However, TDF induced lactic acidosis has never been reported in CHB mono-infected patients. Patient concerns: A 59-year-old man received TDF for hepatitis B associated with cirrhosis. After ten days of TDF administration, nausea, vomiting and abdominal pain developed. High anion gap acidosis with elevated lactate level (pH 7.341, pCO2 29.7 mmHg, HCO3 - 15.6mmHg, lactate 3.2mmol/L, anion gap 15.4 mEq/L) was developed. Diagnosis: With no infection, normal diagnostic paracentesis, and urinalysis together with high anion gap and increased blood lactate levels suggested lactic acidosis. Interventions: TDF was stopped, and haemodialysis was performed to control lactic acidosis. Outcomes: Although stopping TDF instantly and treating lactic acidosis using hemodialysis, the patient died. Lessons: Although, Fatal lactic acidosis is very rare in TDF patient, however, decompensated cirrhotic patients should be closely observed to keep the possibility of lactic acidosis in mind.